Tumor Necrosis Factor Alpha Increases Human Cerebral Endothelial Cell Gb(3) and Sensitivity to Shiga Toxin - Eisenhauer, Patricia B. (American Society for Microbiology, 2001)
Hemolytic uremic syndrome (HUS) is associated with intestinal infection by enterohemorrhagic Escherichia coli strains that produce Shiga toxins. Globotriaosylceramide (Gb(3)) is the functional receptor for Shiga toxin, and tumor necrosis factor alpha (TNF-α) upregulates Gb(3) in both human macrovascular umbilical vein endothelial cells and human microvascular brain endothelial cells. TNF-α treatment enhanced Shiga toxin binding and sensitivity to toxin. This upregulation was specific for Gb(3) species containing normal fatty acids (NFA). Central nervous system (CNS) pathology in HUS could involve cytokine-stimulated elevation of endothelial NFA-Gb(3) levels. Differential expression of Gb(3) species may be a critical determinant of Shiga toxin toxicity and of CNS involvement in HUS.